A Brief Introduction to Body-Oriented Parametric Design for 3D-Printed Fashion and Textiles. (2nd January 2022) - Lin, Mingjing
Abstract: This paper presents the introduction to the author's PhD thesis titled, Interfashionality: Body-oriented Parametric Design and Parametric Thinkign 2.0 for 3 D-printed Fashion and Textiles . The paper firstly introduces the author's research motivation, which is followed by theoretical discussions around and design examples of fashion and textile digitalization, as well as 3 D-printed fashion and textiles. The author then introduces the important implication of parametric design for creating 3 D-printed fashion and textiles. In this section, through analyzing the self-organized conference, Digital Fashion-3D Printing for Designer, and through intensive discussions of the origin of parametric design and its adoption in fashion, the author then summarizes the scope of the research. This paves the way for a concrete research question, five research aims, research structure (model of the research) and thesis structure.